ANALISIS PEMAHAMAN LAPORAN KEUANGAN PADA PELAKU UMKM - Nursasi, Enggar; Stanley, Daniel; Sudiarto, Edi (Inspirasi Ekonomi : Jurnal Ekonomi Manajemen, 2023)
The purpose of this study is to analyze the understanding of MSME business actors on financial statements. The object of this research is the MSME entrepreneurs of Dinoyo ceramic village in Malang. The sampling using purposive sampling with the samples 30 respondents. The processing data using smartpls 3. The result of this research is there is the measurement business variable not affect on the understand of financial statement, the experience of business variable affects on the understand of financial statement, and the level of educational variable not affect on the understand of financial statement.